Analysis of the Use of The Merdeka Teaching Platform For Quality Learning In The Implementation of the Merdeka Curriculum - Situmorang, Eduward; Gultom, Binsar Tison (Journal of Economics Education and Entrepreneurship, 2024)
This research aims to determine the use of the independent teaching platform for the quality of learning of high school Economics teachers in the city of Pematangsiantar. The government provides this platform as a reference, collaboration forum and quality content. The Merdeka Mengajar platform is an important pillar in building better education. This research was carried out for high school level Economics teachers. The data collection technique uses a questionnaire using a Likert scale. The research method used is quantitative descriptive research. The population of this study were all Economics teachers at Senior High School (SMA) level in the city of Pematangsiantar. The sample was selected using purposive sampling with a sample size of 20 respondents. This research was conducted from January to February 2024. Data collection techniques used questionnaires. Data analysis uses the t test and significance values to see the use of the independent teaching platform for the quality of economics teacher learning. Based on the results of the data processing, a significance value of 0.000 was obtained and this figure is smaller than 0.05, therefore it can be concluded that there is an influence of the independent teaching platform variable (x) on the quality of economics teacher learning (y). Furthermore, to provide other supporting evidence, it can be seen from the calculated t and t table values in the processed data. The t value is 8.265 and the t table value is 2.10092. Because the calculated t value is greater than the t table, it can be concluded that there is an influence of the independent teaching platform on the quality of learning. The results of the research show that there is a significant influence in terms of the use of the independent teaching platform on the learning quality of high school economics teachers in the city of Pematangsiantar in implementing the independent curriculum.